Differences between homeless women and men before and after the transition from shelter to community living: A longitudinal analysis. (15th April 2019) - de Vet, Renée; Beijersbergen, Mariëlle D.; Lako, Danielle A. M.; van Hemert, Albert M.; Herman, Daniel B.; Wolf, Judith R. L. M.
Abstract: Social quality is the extent to which people are able to participate in social relationships under conditions which enhance their well‐being, capacities and potential and enables them to shape their own circumstances and contribute to societal development. We assessed whether women in homeless shelters differed from men on social quality factors that constitute the quality of their daily life and whether factor scores changed at a different rate for women and men after shelter exit. Data were collected as part of a randomised controlled trial. In 18 shelters across the Netherlands, 183 participants were recruited between December 2010 and December 2012 and followed for 9 months. Adults were eligible if they were about to move from shelter to (supported) independent housing and their shelter stay had been shorter than 14 months. At baseline, women were significantly younger than men. They were more likely to have children, to have minor children staying with them, to be lower educated, to be unemployed and to have been victimised than men. Women had used more services and reported lower self‐esteem, less satisfaction with health and empowerment and higher psychological distress. They were less likely than men to have used alcohol excessively or cannabis. We found no significant differences between women and men in changes over time on the social quality factors. As women were disadvantaged at baseline compared to men regarding many factors, we concluded that women in homeless shelters are a particularly vulnerable group. Moreover, an opportunity remains for shelter services to improve women's social quality during and after their shelter stay.